The Social Worker as a Full-fledged Member of a Multidisciplinary Cooperation within the Czech Prison System - Stárek, Lukáš; Víšek, Jiří (Social Welfare: Interdisciplinary Approach, 2022)
The legislative amendment to the external differentiation of prisons in the Czech Republic since 2017 mostly stems from the need to create a modern penitentiary rehabilitation of persons serving prison sentences. The fundamental aim is to ensure those conditions that contribute to the resocialisation of said persons and lower t he risk of recidivism. What is emphasised in the context of this amendment is the greater significance of the multidisciplinary teams that work with prisoners as well as social work in prisons. The aim of this paper is thus to highlight the aspect of the importance of social work as a suitable, modern tool used by specialists, i.e. the social workers who become agents of aid or support for persons serving sentences. Our research was conducted using the qualitative method. It specifically comprised five interviews with social workers in the pre-release unit in prisons across the Czech Republic.